Podcast dalam Chanel Youtube Hidayatullah Tv Menjadi Sumber Pengajaran, Sumber Belajar dan sebagai Persiapan Contributor Mualaf - Alwazir Abdusshomad (PALAPA, 2022)
This study aims to determine the relevance of Podcasts in the Hidayatullah TV Youtube Chanel as a source of teaching, learning resources and as a preparation for converts to converts. The research used is qualitative with primary sources in the form of 3 (three) Video Podcasts on Chanel Hidayatullah TV, namely (1) Video with the title "The Blind Genius Child of a Hindu Figure Finally Converts to Islam, (2) Video with the Title Lamongan! Her husband is a fanatical Christian, prays because his wife is not tired of praying, and (3) a pastor in Ponorogo, his family converted to Islam”. Secondary sources are in the form of scientific journals, books, Youtube videos, articles, and online news. From the results of the study, it was found that the Hidayatullah Tv Youtube Podcast could be a teaching resource, a learning resource and as a preparation for converts to converts before appearing in the podcast.